SISTEM PEWARISAN KETERAMPILAN MENGUKIR WARGA TRANSMIGRASI BALI DI PROVINSI SULAWESI TENGAH - Komang Wastra; I Wayan Seriyoga Parta; Hasdiana Hasdiana (Universitas Pendidikan Ganesha, 2022)
This study intends to determine the Inheritance System of carving skills for Balinese transmigration residents in Sari Bhuana Village, Toili District, Banggai Regency, Central Sulawesi Province. And to study the inheritance system of carving as an academic study, so that it can become a knowledge for the Balinese Transmigration community, especially in developing carving through the inheritance system. The method used in this research is descriptive qualitative, data collected by observation, interviews and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. The results of this study indicate that the inheritance system for carving Balinese transmigration skills in Sari Bhuana Village is a horizontal inheritance system (horizontal transmission) where this inheritance system occurs within the scope of peers or playmates, while still having the same cultural and artistic relationship. With a unique learning process for someone who has mastered the skill of carving, to become a teacher or mentor by being involved in every carving activity he does. Keywords: inheritance system, carving, craftmanship, sari buana village